Short-term resistance and plyometric training improves eccentric phase kinetics in jumping - Kijowksi, K. N.; Capps, C. R.; Goodman, C. L.; Erickson, T. M.; Knorr, D. P.; Triplett, N. T.; Awelewa, O. O.; McBride, J. M. (The Journal of Strength and Conditioning Research, 2015)
The purpose of this investigation was to examine the effect of an abbreviated resistance and plyometric training program on force- and power-time curve variables during jumping. Nineteen male subjects were assigned to either a training (n = 9) or control group (n = 10). Training consisted of performing 3 sets of 3 repetition squats (90% of 1 repetition maximum [RM]) and 5 sets of 6 repetition drop jumps from 40 cm twice per week for 4 weeks. A 1RM in the squat and countermovement (CMJ) and static jump (SJ) performance was assessed before and after training. Several variables were analyzed for individual subject force- and power-time curves for the jumps. Average force- and power-time curves for all subjects combined were also analyzed. Absolute and relative squat strength significantly increased in training group (p = 0.05). Calculation of variables from individual subject force-time curves during the CMJ indicated a significant decrease in eccentric time, minimum force, and eccentric impulse and significant increase in eccentric rate of force development in training group. Analysis of individual power-time curves in the CMJ also revealed a significant decrease in minimum power and eccentric work and a significant increase in eccentric rate of power development. No significant changes occurred in the variables measured for the SJ. The results of this study indicate that short-term strength and plyometric training may preferentially influence eccentric performance variables during jumping in comparison with longer term training enhancements to the concentric phase performance.